2003
DOI: 10.5144/0256-4947.2003.36
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. Open Adrenalectomy: Experience at King Faisal Specialist Hospital and Research Centre, Riyadh

Abstract: Background:The laparoscopic approach for adrenalectomy is now widely accepted and preferred over the conventional open approach. We describe our experience of adrenalectomy and compare the results of open and laparoscopic approach. Patients and Methods: From March 1999 to March 2002, we performed 23 adrenalectomies. An anterior transabdominal approach was used for the open procedure, and a lateral transperitoneal approach for the laparoscopic procedure. Data from both groups were analyzed and compared. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…A recent review from the region showed that the total number of Robot-assisted surgery in the Middle East is still low and there are 19 da Vinci Surgical Systems installed in Saudi Arabia; 6 in Qatar; 3 in the United Arab Emirates; 2 in each of Kuwait and Lebanon; and only 1 in Egypt ( 18 ). Apart from the comparison of laparoscopic and open surgery in a small sample size, no published data is comparing the 3 surgical approaches for adrenal pathology from the Arab Middle East ( 19 ). The present study aims to describe the frequency, clinical presentation, and outcomes associated with the 3 surgical approaches in patients who underwent adrenalectomy (open, robotic, or laparoscopic) for adrenal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review from the region showed that the total number of Robot-assisted surgery in the Middle East is still low and there are 19 da Vinci Surgical Systems installed in Saudi Arabia; 6 in Qatar; 3 in the United Arab Emirates; 2 in each of Kuwait and Lebanon; and only 1 in Egypt ( 18 ). Apart from the comparison of laparoscopic and open surgery in a small sample size, no published data is comparing the 3 surgical approaches for adrenal pathology from the Arab Middle East ( 19 ). The present study aims to describe the frequency, clinical presentation, and outcomes associated with the 3 surgical approaches in patients who underwent adrenalectomy (open, robotic, or laparoscopic) for adrenal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The indications for adrenalectomy were pheochromocytomas in five (23%) patients, Conn’s adenoma in 6 (28%) patients, Cushing’s disease in three (14%) patients, and ACC in only one (0.4%) patient. The study concluded that laparoscopic adrenalectomy is a safe procedure for most adrenal pathology [ 9 ]. Our understanding of the prevalence of adrenal tumors, incidence rate, types, treatment methods, and age group in Saudi Arabia is limited and insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…The adrenal glands are ideal for the use of the technique, as they are small retroperitoneal organs that were traditionally approached through a relatively large abdominal, flank or thoracoabdominal incision. Laparoscopy enabled surgeons to use safe and effective procedures, and offers patients all the advantages of minimally invasive surgery, with decreased blood loss, less post operative pain, decreased hospital stay and faster recovery [3–6] . Laparoscopy has had an effect on adrenal surgery over the last two decades, with more adrenalectomies being performed, the lesion size as an indication for surgery decreased, and more incidentalomas and benign tumours being resected [7–10] .…”
Section: Introductionmentioning
confidence: 99%